On the evaluation of climate change mitigation in the colombian energy sector (2018)
"Climate change demands immediate actions from all countries towards a fully decarbonized world by the end of this century. Consequently, Colombia is required to set and undertake locally defined actions and strategies to decarbonize its national economy. These actions must be defined based on strong scientific and quantitative evidence. This raises the need to have local modeling tools producing such information to enable the country to address climate change in the most effective way according to their possibilities, while minimizing the potential negative impacts on welfare, poverty and, in general, development. This research aimed to develop modeling tools to produce quantitative information and to analyze mitigation options. This approach aims to support stakeholders and policymakers, to the extent of possible, in the informed decision-making process, concerning climate change mitigation in Colombia. Three types of modeling tools and analyses were developed. First, the estimation of the Colombian GHG's reduction path as required by science and equity towards global climate stabilization at 2°C and 1.5°Cwas performed. Additionally, the gross emissions baseline for the Colombian energy sector was calculated using Kaya factors. Second, two models (i.e., transportation and power sector) were developed to represent sectoral activities to assess the technical feasibility and costs of undertaking mitigation actions planning. Finally, a set of tools and methodologies dedicated to assessing the associated macroeconomic impacts from the implementation of sectoral mitigation actions were developed. On one hand, a soft-linking between an energy sector model and a General Equilibrium Model (GEM) was performed to assess macroeconomic impacts of a carbon tax applied to energy. On the other hand, a tool was constructed to produce marginal abatement cost curves from the information produced by sector-specific models."--Tomado del Formato de Documento de Grado.